FRI0116 Hypermobility in sistemic lupus erythematosus. (1st June 2001) - Guma, M; Olive, A; Forcada, J; Duró, JC; Roca, J; Holgado, S; Casado, E; Tena, X
Abstract : Background: Objectives: To investigate hypermobility in patients in systemic lupus erythematosus (SLE). Methods: Setting: University Hospital; 80 patients with SLE (1999 ACR criteria), 90% females and 10% males, mean age 44 ± 16, who regularly attended a specialist SLE clinic were examined. Control group was composed of 280 patients attending a general practitioner office, 70% females and 30% males, mean age 46 ± 19. Joint laxity was measured according to Carter and Beighton criteria (total score 4 or more). A regression analysis was performed (SAS statistical package). Results: Forty-eight% or patients with SLE and 12% of the control group were hypermobile. Regression analysis showed that after adjustment for the age and sex, patients with SLE were more hypermobile (Odds Ratio:5). Neither the clinical and analytical profile nor the use of corticosteroids was related to hipermobility. Conclusion: Patients with SLE are more hypermobile that control group. No clinical or analytical profile is related. Steroids are not related to the presence of hypermobility in patients with SLE.